A Tiered Geospatial Sensing Framework for Context-Aware Content Delivery: Application in Scriptural Information Systems - Bagas Imanuel Pasaribu; Yudhy Setyo Purwanto (Universitas Nusantara PGRI Kediri, 2026)
Background: Current digital Bible applications predominantly utilize